"Evaluación de cinco insecticidas químicos bajo dos métodos de aplicación para el control sw gusano cogollero (Spodoptera) frugiperda en el cultivo de maíz en la finca experimental la María de la zona de Mocache" - Mayorga Santana, Félix Eduardo (2012)
The present investigation was carried out in the experimental property The María", of the State Technical University of Quevedo, located in the Km. 7 of the Road Quevedo - The Connection, in the Canton Mocache, County of The Rivers. It is among the geographical coordinates of 01° O6 ' of South latitude and 79° 29'de longitude West. To a height 73 meters on the level of the sea. You outlines the general objective: To evaluate the effect of five insecticides chemical low two application methods for the control of worm cogollero in the cultivation of corn, and the specific ones: To determine which of the insecticides and under that application method is to be more efficient in the control of worm cogollero, to determine the yield of the cultivation in function of the treatments and one of the treatments will improve the relationship I benefit cost. Subject to the following hypotheses: At least one of the treatments will be superior to the witness in the control of the worm cogollero, at least one of the treatments will determine a better yield of the cultivation and One of the treatments will improve the relationship I benefit cost. The treatments were constituted by five insecticides of chemical synthesis that are: (Abamectina (Necmectina 1.8 Ec) 300 cc/ha), (Lufenuron (Match 50 Ec) 0,4 lt /ha), (profenofos (Curacron 500Ec)0,8 lt/ha), (Engeo 200 cc/ha), ................................................................................